The impact of perceived organizational cronyism on decision-making: The moderating role of ethical organizational culture - Hamza Khraim (Problems and Perspectives in Management)
One of the primary responsibilities of managers is to make informed decisions that promote company progress and enhance performance. Unfortunately, not all managers adhere to appropriate decision-making standards. Some managers may resort to subjective criteria instead of relying on objective performance metrics. The purpose of this study is to investigate employees’ perceptions of cronyism and how organizational cronyism influences decision-making in pharmaceutical manufacturing companies in Jordan. A quantitative approach was employed, using a structured questionnaire to gather employee responses. The questionnaires were collected from employees of the top five pharmaceutical companies, which are considered the most dynamic and competitive in the Jordanian market. A total of 452 usable questionnaires were included in the analysis. The results indicate that all three dimensions of organizational cronyism, including paternal cronyism (β = 0.295, t = 5.382, p > 0.000), in-group bias (β = 0.277, t = 3.514, p > 0.000), and reciprocal exchange of favor (β = 0.321, t = 3.866, p > 0.000), have a significant impact on decision-making. Regarding the moderating impact of ethical organizational culture, the results reveal a weak impact on the relationship between the dimensions of organizational cronyism and organizational culture. Unprejudiced decision-making can be a crucial factor in fostering an ethical culture and reducing organizational cronyism.